2017
DOI: 10.1111/andr.12450
|View full text |Cite
|
Sign up to set email alerts
|

Congenital bilateral absence of the vas deferens as an atypical form of cystic fibrosis: reproductive implications and genetic counseling

Abstract: Congenital bilateral absence of the vas deferens (CBAVD) is found in 1% to 2% of males with infertility and is present in 6% of obstructive azoospermia cases. Nearly 95% of men with cystic fibrosis (CF, an autosomal recessive disorder) have CBAVD. There are genetic links between CBAVD and CF. Some mutations in the gene encoding cystic fibrosis transmembrane conductance regulator (CFTR) can lead to CBAVD as a monosymptomatic form of CF. With the use of assisted reproductive techniques (ART), especially testicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 90 publications
(125 reference statements)
0
58
0
6
Order By: Relevance
“…As a primary factor leading to male reproductive disorders, CBAVD is a key component of obstructive azoospermia (OA) and is perceived as a mild form of CF (de Souza, Faucz, Pereira-Ferrari, Sotomaior, & Raskin, 2018). Previous studies have identified the positive association between CBAVD and CFTR mutations.…”
mentioning
confidence: 99%
“…As a primary factor leading to male reproductive disorders, CBAVD is a key component of obstructive azoospermia (OA) and is perceived as a mild form of CF (de Souza, Faucz, Pereira-Ferrari, Sotomaior, & Raskin, 2018). Previous studies have identified the positive association between CBAVD and CFTR mutations.…”
mentioning
confidence: 99%
“…These findings raise questions about the routes and the mechanisms by which mutations in the CFTR gene lead to diverse genetic problems. Several groups who have examined large cohorts of patients with CFTR mutations have reported some genotype–phenotype relationships (de Souza et al, 2018; Yuan et al, 2019). Yet, the molecular mechanisms by which the CFTR mutations lead to problems of organogenesis remain ununderstood.…”
Section: Discussionmentioning
confidence: 99%
“…Extending these earlier findings, we suggest that ENaC has a role in the function of vas deferens smooth muscle cells that remain to be defined. (de Souza et al, 2018;Yuan et al, 2019). Yet, the molecular mechanisms by which the CFTR mutations lead to problems of organogenesis remain ununderstood.…”
Section: Functional Significance Of the Localization Of Aqp9 Enacmentioning
confidence: 99%
“…The life expectancy of people with CF has been increasing due to improved treatments [4,9], which has resulted in an increasing number of men and women with CF living into adulthood and wanting to have children. In both cases, it is recommended that the partner is tested for cystic fibrosis transmembrane conductance regulator (CFTR) mutations to allow appropriate discussions regarding prenatal testing and pre-implantation genetic diagnosis [10,11].…”
Section: Fertility In Cf and Bronchiectasismentioning
confidence: 99%
“…It is well known that most men with CF (95%) are infertile because of blockage or absence of the vas deferens, which requires in vitro fertilisation (IVF) intervention for pregnancy [10]. In contrast, although CFTR is expressed in the cervix [12] and the water content of cervical mucous does not show the normal menstrual cycle variation, the fallopian tubes remain patent in the majority of adult women with CF [13].…”
Section: Fertility In Cf and Bronchiectasismentioning
confidence: 99%